Über die Verteilung der Werte von multiplikativen Funktionen - Kubilius, J.; Juškys, Z. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Кубилюс, З. Юшкис. О распределении значений мультипликативных функцийJ. Kubilius, Z. Juškys. Multiplikatyvinių funkcijų reikšmių pasiskirstymas